2014
DOI: 10.1007/s00586-014-3582-6
|View full text |Cite
|
Sign up to set email alerts
|

Axial T1ρ MRI as a diagnostic imaging modality to quantify proteoglycan concentration in degenerative disc disease

Abstract: Purpose The aim of the study was to investigate if axial T1ρ MR images had similar accuracy as established sagittal T1ρ MRI for the assessment of proteoglycan concentration and content in intervertebral degenerated discs (IDDs). Methods T1ρ and T2-weighted MR images of 12 intervertebral discs (IVDs) from 3 harvested human lumbar spines (levels L1–L2 to L5–S1) were grouped across their degenerative grade (Pfirrmann scores) and analyzed using a 3T MRI scanner in the axial and sagittal views. Post-processing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Direct, in vivo evaluation of disc mechanical properties is possible using emerging technologies such as magnetic resonance elastography . Where direct evaluation is impossible, assessments of extracellular matrix composition and organization through biochemical and histological assays, or imaging (eg, MRI or contrast‐enhanced CT), represent important surrogates for mechanical function …”
Section: Selecting Physiologically and Clinically Relevant Efficacy Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct, in vivo evaluation of disc mechanical properties is possible using emerging technologies such as magnetic resonance elastography . Where direct evaluation is impossible, assessments of extracellular matrix composition and organization through biochemical and histological assays, or imaging (eg, MRI or contrast‐enhanced CT), represent important surrogates for mechanical function …”
Section: Selecting Physiologically and Clinically Relevant Efficacy Mmentioning
confidence: 99%
“…For effective clinical translation it will be important to stratify patient cohorts, for example using sophisticated magnetic resonance imaging techniques [33][34][35][36][37] and quantification of circulating biomarkers 38 to select suitable candidates for treatment. The opportunity for cellbased therapy may be most appropriate at the early stage of the degenerative cascade, prior to the onset of advanced disc degeneration coupled with endplate calcification and extensive annular degeneration.…”
Section: Patient Selection: Even the Best Therapy Won't Succeed If mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative MRI using the relaxation times T1 and T2, the magnetization transfer ratio, and the apparent diffusion coefficient facilitates noninvasive assessment and diagnosis of changes including disc matrix composition (water, proteoglycan, and collagen), integrity (percent collagen denaturation), and biomechanics which have been shown to correlate strongly with disc tissue degeneration . Axial T1ρ MRI has been utilized to quantify proteoglycan concentrations which can be related to Pfirrmann grading, while chemical exchange saturation transfer (CEST) MRI has been employed for in vivo IVD pH level‐dependent imaging without the need for exogenous contrast agents . T2 mapping has been observed to be particularly sensitive to early and intermediate stage biochemical and mechanical degenerative changes compared with T1ρ in an ex vivo chymopapain digestion lapine model, while both parameters appear to be sensitive to advanced degenerative changes .…”
Section: The Role Of the Disc Microenvironmentmentioning
confidence: 99%
“…Early studies showed a significant correlation between the T1ρ relaxation time and the loss of proteoglycan molecules in cartilage [8]. In the spine, T1ρ relaxation times showed relevant correlations with the amount of proteoglycans in the extracellular matrix of the lumbar disc, with longer relaxation times indicating greater amounts of proteoglycans [7,9,10]. In addition, T1ρ relaxation times correlated significantly with the water content in the intervertebral lumbar disc [7].…”
Section: Introductionmentioning
confidence: 99%